Oro inför arbetslivet hos sistaårsstudenter på universitetet. - Karltorp,Johanna; Fröjd,Elin (2018)
Anxiety and worry among young adults is a relevant topic today. In this study, the worry felt by last year university students as they enter the workforce were examined, and whether or not this worry can be due to self-efficacy, trait anxiety and/or branch related work experience. The study was based on a cross sectional poll, where the sample was 93 students enrolled at Lund University. Thirty six percent felt worried and anxious with regards to the future. Thirty four percent wholly, or partially, agreed that their future in the work market was unsure. Thirty nine percent wholly, or partially, agreed with that they felt worried over not getting a job after concluding their studies. Only a weak correlation between worry for the future and general self-efficacy and trait anxiety was found. The mean value of worry for the future was lower in those students with relevant work experience connected to their studies. This study further shows that more than one third of the students who participated experienced worry and anxiety for the future and worry for their future on the work market and this can, to a high extent, be considered a problem which requires further research.
Keywords: generell self-efficacy; egenskapsångest; framtidsoro; arbetslivserfarenhet; student